2001
DOI: 10.1007/s00432-001-0299-9
|View full text |Cite
|
Sign up to set email alerts
|

Progesterone receptor status of breast cancer metastases

Abstract: It seems that the lack of positive progesterone receptors in metastasis (0/8) and conversion from PR+ primary to PR- metastasis (5/8) may be important in describing the non-responder phenotype. We obtained a similar progression-free interval in patients with progesterone receptor-positive/negative primary tumors, but a longer progression-free interval in the patients with progesterone receptor-positive metastases ( n=9) than with negative ones ( n=14), indicating the possibility of using steroid receptor conte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 12 publications
1
14
0
1
Order By: Relevance
“…Previous studies (all using the 10% threshold when indicated) reported PR conversion rates from 28% to 61%, again higher than in the present study. The explanation for this may be similar to what has been mentioned above: previous studies did not restain both the primary and metastatic lesions [5,8,10,11], used ligand-binding assays [2,7,10], or included bone metastases [2,6,8-10,12]. Further, our series is much larger with 233 compared to most previous PR studies with 9 to 59 cases.…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…Previous studies (all using the 10% threshold when indicated) reported PR conversion rates from 28% to 61%, again higher than in the present study. The explanation for this may be similar to what has been mentioned above: previous studies did not restain both the primary and metastatic lesions [5,8,10,11], used ligand-binding assays [2,7,10], or included bone metastases [2,6,8-10,12]. Further, our series is much larger with 233 compared to most previous PR studies with 9 to 59 cases.…”
Section: Discussionsupporting
confidence: 58%
“…The explanation for this finding may be that previous ERα studies did not restain both the primary and metastatic lesions [3,5,8,10,11], used ligand-binding assays [2,3,7,10] (where the result is influenced by differences in the percentage of non-tumor cells in the samples), or included bone metastases that may suffer from false negative IHC results due to decalcification [2,4,6,8-10,12]. In addition, with 233 cases our series is much larger than most previous ERα studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In biopsies from patients who developed resistance to tamoxifen, changes in hormone receptor status, as well as in other signalling pathway molecules, such as HER2, have also recently been documented [18]. Similarly, to ER, and perhaps even at a higher rate, a significant proportion of PR-positive tumours also lose PR expression in their metastasis [19], and loss of PR in sequential biopsies, particularly with intervening endocrine therapy, is associated with poorer survival as compared with patients retaining PR [20]. Nevertheless, trials in metastatic disease suggest that these tumours still benefit from endocrine therapy [21], although some data suggest that they may have a somewhat worse clinical outcome than ER-positive tumors [22].…”
Section: Solitary Hypothalamus Triple Negative Metastasis From Luminamentioning
confidence: 96%
“…HER2 может являться ведущим фактором в прогрессии опухоли, являясь альтернативным путем выживания, либо уменьшая уровень РЭ, делая опухоль менее чувствитель-ной к эстрогену [43,72]. С другой стороны, РП теряются опухолью после начала эндокринной терапии гораздо чаще, нежели РЭ, в связи с чем опухоль становится более агрессивной, а у пациен-тов с такими опухолями выживаемость хуже, чем у паци-ентов, больных опухолями, сохранивших РП [73,75]. Получение ответа на лечение одним из видов эндокринной терапии после прогрессии заболевания на фоне лечения другим видом -исторически известный факт, являющий-ся ключевым в лечении метастатической болезни при РМЖ [7].…”
Section: эндокринная терапияunclassified